Evaluation of students' receptiveness and response to an interprofessional learning activity across health care disciplines: An approach toward team development in healthcare - M.P. Judge; E.C. Polifroni; A.T. Maruca; M.E. Hobson; A. Leschak; H. Zakewicz (International Journal of Nursing Sciences, 2015)
Objective: This investigation evaluated if exposure to interdisciplinary education improves student readiness for interprofessional learning, fundamental to healthcare team development. Methods: A pre-test post-test design was used to evaluate 308 students from dental medicine, dietetics, medicine, nursing, pharmacy and physical therapy. The Readiness for Interprofessional Learning Scale (RIPLS) was used to evaluate student responsiveness to interprofessional education. Results: Nursing RIPLS mean post-test score was higher compared to the pre-test score (p = 0.020). Pharmacy students had higher RIPLS mean pre-test score compared to medical (p = 0.010) and nursing students (p = 0.018). RIPLS mean pre-test score was higher for dietetics than medical students (p = 0.022). Conclusions/Implications: Interdisciplinary learning enhances readiness for interprofessional learning with nursing students. Pharmacy and dietetics students demonstrated a higher level of readiness for interdisciplinary learning compared to other disciplines. Identification of factors influencing readiness for interprofessional learning are key to developing learning strategies targeted to improve teamwork, quality of care and patient outcomes.